2018
DOI: 10.1111/ffe.12931
|View full text |Cite
|
Sign up to set email alerts
|

The effect of adherent thickness on fatigue life of adhesively bonded joints

Abstract: The effect of adherent thickness on the fatigue performance, fatigue limit, and failure mode of adhesively bonded thin aluminum single lap joint (SLJ) was experimentally and numerically investigated. High‐cycle fatigue tests were performed, and fatigue life was estimated using various fatigue criteria and finite element modeling. Based on the experimental results, increase in adherent thickness leads to increase in fatigue limit. In addition, failure location changes from adhesive to adherent by increasing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…It shows that the unbonded area within the adhesive layer has a similar effect as overlap length. Increasing the unbonded area decreases the crack growth life due to the shorter crack growth length, which explains why fatigue failure life of weld‐bonded joints is smaller than that of similar adhesive‐bonded joints 16 . However, the initiation life remains similar in three kinds of joints, indicating the insignificant effect of unbonded area on crack nucleation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It shows that the unbonded area within the adhesive layer has a similar effect as overlap length. Increasing the unbonded area decreases the crack growth life due to the shorter crack growth length, which explains why fatigue failure life of weld‐bonded joints is smaller than that of similar adhesive‐bonded joints 16 . However, the initiation life remains similar in three kinds of joints, indicating the insignificant effect of unbonded area on crack nucleation.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, the total fatigue failure of an adhesive‐bonded joint consists of crack initiation 16,17 and subsequent crack growth 18–21 . It has been reported that the proportion of crack growth life will increase with increasing load levels 22–24 .…”
Section: Introductionmentioning
confidence: 99%
“…Afendi et al 33 reported that the apparent tensile modulus of adhesive layer of the SAJs is about 1.5–5 times higher than that of the bulk epoxy, and the strength of the joints was increased with decreasing bond thickness. Shahani and Pourhosseini 17 pointed out that the increase in the adhesive thickness results in increasing stress concentration and hence, decreasing fatigue lives and strength. Numerically, Davies et al 34 found that the stress state exhibited larger stress concentration factors for tensile loading in the adhesive joints with thicker bondline, which can interpret their lower strength.…”
Section: Resultsmentioning
confidence: 99%
“…The adhesive layer thickness has a detrimental influence on the mechanical characteristics of the bonded joints 18 . Ferro and Berto 19 have investigated the influence of adhesive material thickness on the failure stress and average strain energy density of butt joint with diameter of 15 mm.…”
Section: Introductionmentioning
confidence: 99%
“…The adhesive layer thickness has a detrimental influence on the mechanical characteristics of the bonded joints. 18 Ferro and Berto 19 have investigated the influence of adhesive material thickness on the failure stress and average strain energy density of butt joint with diameter of 15 mm. They have found that the critical value of the average strain energy density is independent on the adhesive layer thickness and hence, can be used for bonded joint design.…”
Section: Introductionmentioning
confidence: 99%